EMPIRICAL STUDY OF MANAGEMENT OF EDUCATION BASED ON PRINCIPAL MANAGEMENT SYSTEM TO IMPROVE THE QUALITY OF EDUCATION IN ELEMENTARY SCHOOLS - Kurniawan, Adi Cahyadi; Muslihin, Heri Yusuf; Indihadi, Dian (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the management of education based on the principal's managerial system in an effort to improve the quality of education in elementary schools. The method used is a literature study, which examines various sources related to the functions, duties, and responsibilities of the principal, as well as the managerial skills needed. The function of the principal as an educational leader is very crucial in creating a conducive learning environment. His duties and responsibilities include planning, organizing, implementing, and evaluating educational programs. In addition, the principal's managerial skills are divided into four categories: conceptual skills that enable the principal to formulate an educational vision and mission; administrative skills that support resource management; human skills that are important in building interpersonal relationships; and technical skills needed to implement educational policies effectively. The results of this study indicate that good mastery of managerial skills by the principal contributes significantly to improving the quality of education in elementary schools. This study is expected to provide insight for policy makers and education practitioners in optimizing the role of the principal in educational management. This study also highlights the importance of training and professional development for principals to improve their managerial skills. With the right training, principals can be more effective in carrying out their functions and responsibilities, and are able to face the challenges that arise in the world of education. In addition, collaboration between principals and teachers, parents, and the community is also a key factor in creating a quality education ecosystem. Through a good managerial approach, it is hoped that elementary schools can achieve higher education goals and produce graduates who are ready to face future challenges. This study provides recommendations for the development of training programs that focus on improving the managerial skills of principals as a strategic step in improving the quality of education at the elementary level.